A systematic series of fluorescence chemosensors with multiple binding sites for Hg(ii) based on pyrenyl-functionalized cyclotriphosphazenes and their application in live cell imaging. (31st July 2018) - Tümay, Süreyya Oğuz; Uslu, Aylin; Ardıç Alidağı, Hüsniye; Kazan, Hasan Hüseyin; Bayraktar, Cansu; Yolaçan, Tutku; Durmuş, Mahmut; Yeşilot, Serkan
Abstract : A systematic series of fluorescence chemosensors based on cyclotriphosphazene derivatives were designed, synthesized, and evaluated for their sensing behaviors toward metal ions. Abstract : A systematic series of fluorescence chemosensors (1–3 ) having one, two and three-metal binding sites based on cyclotriphosphazene derivatives bearing bis-, tetra- and hexakis-2-(pyren-1-yl methylene amino) phenoxy units, respectively, were designed, synthesized, and evaluated for their sensing behaviors toward metal ions using UV/Vis and fluorescence spectroscopies. Upon the addition of Hg 2+ in both the absence and presence of competitive metal ions, the chemosensors revealed highly selective and sensitive "turn-on" emission enhancement based on the combined effects of chelation-enhanced fluorescence (CHEF), CN isomerization and intramolecular pyrene excimer formation, as well as a color change from yellowish to colorless, which was readily detected by the naked eye. According to the Job plot method, the complexation ratios of chemosensors (1–3 ) with Hg 2+ were found to be 1 : 1, 1 : 2 and 1 : 3 (ligand : metal), respectively, consistent with the proposed number of metal binding sites. Furthermore, the binding modes of chemosensors (1–3 ) with Hg 2+ were supported by 1 H NMR spectroscopy. The increasing complexation ratios from 1 : 1 to 1 : 3 for chemosensors (1–3 ) enabled proportionally decreasing values for the detection limit (LOD) with 0.223 μM, 0.114 μM and 0.050 μM, respectively. The cytotoxicity and fluorescence microscopy experiments also demonstrated that chemosensors (1–3 ) are non-cytotoxic, and can be used as fluorescence imaging sensors for Hg 2+ in living cells.